2020
DOI: 10.1016/j.smhs.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral strategies to prevent and mitigate COVID-19 infection

Abstract: The single stranded RNA virus SARS-CoV-2 has caused a massive addition to the already leading global cause of mortality, viral respiratory tract infections. Characterized by and associated with early and deleteriously enhanced production of pro-inflammatory cytokines by respiratory epithelial cells, severe COVID-19 illness has the potential to inflict acute respiratory distress syndrome and even death. Due to the fast spreading nature of COVID-19 and the current lack of a vaccine or specific pharmaceutical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 145 publications
(174 reference statements)
0
6
0
3
Order By: Relevance
“…56 Evidence also suggests that prolonged and intense exercise before or during infection is associated with increased morbidity and mortality, especially among those who are not regularly active. 5 Importantly, physical activity reduces the frequency of viral infections. 56,57 Thus, evidence supports an expectation that moderate-intensity physical activity may reduce severity of COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…56 Evidence also suggests that prolonged and intense exercise before or during infection is associated with increased morbidity and mortality, especially among those who are not regularly active. 5 Importantly, physical activity reduces the frequency of viral infections. 56,57 Thus, evidence supports an expectation that moderate-intensity physical activity may reduce severity of COVID-19 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Other findings also concluded that one of the behavioral strategies to prevent and reduce COVID-19 infection is to regularly perform physical activities with moderate intensity and always maintain health protocols such as masks [22]. Although a large number of studies have shown that increasing the power of training suppresses the immune system and increases the rate of viral infection [23], two recent studies report that highintensity interval training (HIIT) does not have an inhibitory effect on immune function [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…So far, no specific antiviral drugs for COVID-19 exist. 6 The mainstay recommended treatments for COVID-19 are as follows: Maintain the autoimmunity of the patients; provide supportive therapies based on clinical symptoms, including oxygen inhalation, supplementation of fluid, nutrition enhancement, immunoregulatory treatment, fever management, and traditional Chinese medicine treatments. If the patients also have combined bacterial infections, concomitant use of antibiotic drugs is used with early symptomatic treatment usually achieving a better prognosis.…”
Section: Recommended Medication and Non-medication Treatments For Covid-19mentioning
confidence: 99%